Combining participatory action research with intervention mapping to develop and plan the implementation and evaluation of a healthy sleep intervention for adolescents - Ann Vandendriessche; Benedicte Deforche; Karlien Dhondt; Teatske M. Altenburg; Maïté Verloigne (Tabriz University of Medical Sciences, 2023)
Background: Adolescents' sleep deteriorated over the last decades, urging the need to develop effective interventions. Using participatory action research (PAR) is a promising and unique approach to target adolescents' sleep. This study aims to describe the process and results of combining PAR and intervention mapping (IM) to guide future researchers on developing and planning of the implementation and evaluation of interventions promoting healthy sleep in adolescents. Methods: In each of three intervention schools (two with general and technical education and one with technical and vocational education), an action team including adolescents (age 13- 15 years, n=max. 12) and a researcher was composed to develop and plan the intervention. During weekly sessions (n=ranging from 23 to 34 per school), the action team went through the six steps of IM. A short PAR was performed with parents (n=7) to develop parental intervention components. Results: Combining PAR and IM resulted in interventions focusing on the importance of healthy sleep, regular sleep patterns and associated behaviors: screen behaviors, physical activity, dietary behavior and relaxation. Several differences in the participatory process (i.e. more guidance needed during brainstorms in the vocational/technical school) and developed intervention (i.e. less intrusive intervention components in the vocational/technical school) were observed between schools. Conclusion: Combining PAR with IM resulted in more extensive interventions than other existing school-based sleep interventions. Future studies should investigate whether a participatory developed sleep intervention could be transferred to another setting using a shorter participatory process.